Ancient and Modern Celebrated Freethinkers : Reprinted From an English Work, Entitled "Half-Hours With The Freethinkers." - Bradlaugh, Charles, 1833-1891; Collins, Anthony, active 19th century; Watts, John (Salt Lake City, UT : Project Gutenberg, 2009)
"Ancient and Modern Celebrated Freethinkers" by Bradlaugh, Collins, and Watts is a compilation of biographies and philosophical doctrines of notable freethinkers, written in the late 19th century. The work presents a catalog of influential thinkers throughout history, like Thomas Hobbes, Voltaire, and Spinoza, exploring their life stories and contributions to the discourse surrounding free thought and skepticism towards established religions. The editors aim to make the thoughts of these remarkable individuals accessible to a broader audience, particularly those who may not have the means to engage with the original writings. At the start of the book, the editors articulate their purpose for compiling the materials, emphasizing a desire to inform readers about key figures in the history of free thought. They outline the biographies to come, which will include summaries of the lives and ideologies of prominent freethinkers like Thomas Hobbes and Lord Bolingbroke, highlighting their struggles against superstition and advocating for rational inquiry. This introduction sets a tone that expresses admiration for the highlighted philosophers while encouraging readers to engage with the ideas that pushed against the boundaries of dogma and religious orthodoxy. (This is an automatically generated summary.)
Thomas Hobbes -- Lord Bolingbroke -- Condorcet -- Spinoza -- Anthony Collins -- Des Cartes -- M. de Voltaire -- John Toland -- Compte de Volney -- Charles Blount -- Percy Byssche Shelley -- Claude Arian Helvetius -- Frances W. D'Arusmont -- Epicurus -- Zeno, the Stoic -- Matthew Tindal -- David Hume -- Dr. Thomas Burnet -- Thomas Paine -- Baptiste de Mirabaud -- Baron d'Holbach -- Robert Taylor -- Joseph Barker.
Release date is 2009-10-06
Produced by David Widger
Keywords: Rationalists -- Biography